2004
DOI: 10.1021/jp0361172
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and One-Dimensional Self-Assembly of Acicular Nickel Nanocrystallites under Magnetic Fields

Abstract: Polycrystalline nickel wires with an average length of 10 µm and diameter of about 200 nm were prepared at 70°C by a hydrothermal process with a 0.25 T magnetic field applied. Studies show that the magnetic field induced one-dimensional assembly of acicular Ni nanocrystallites with dimensions of 200 nm in length and 10-30 nm in diameter, leading to the formation of the polycrystalline nickel wires. Magnetic measurements show saturation magnetization (Ms) of the sample prepared in a 0.25 T external magnetic fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
110
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(113 citation statements)
references
References 29 publications
3
110
0
Order By: Relevance
“…4,5 Accordingly, a series of one-dimension (1D) nickel nanostructures including nanotubes, nanowires, nanorods, nanochains and nanoarrays have been synthesized. [6][7][8][9][10][11][12][13] A variety of one-dimensional (1D) core-shell structures were prepared to enhance the multifunctionality of these materials, and they have exhibited good characters in improving luminescent efficiency, magnetic property and as field effect transistors. [14][15][16][17] Many methods of preparation in high temperature, including a laser ablation method, a high-temperature route and a carbothermal reduction method, have been used to synthesize the core-shell nanomaterials.…”
mentioning
confidence: 99%
“…4,5 Accordingly, a series of one-dimension (1D) nickel nanostructures including nanotubes, nanowires, nanorods, nanochains and nanoarrays have been synthesized. [6][7][8][9][10][11][12][13] A variety of one-dimensional (1D) core-shell structures were prepared to enhance the multifunctionality of these materials, and they have exhibited good characters in improving luminescent efficiency, magnetic property and as field effect transistors. [14][15][16][17] Many methods of preparation in high temperature, including a laser ablation method, a high-temperature route and a carbothermal reduction method, have been used to synthesize the core-shell nanomaterials.…”
mentioning
confidence: 99%
“…It also can be found that the H C and M r values for these two sample are much higher than those for bulk nickel materials (100 Oe, 2.7 emu/g), which also can be attributed to their unique preferred orientation structures [22] and the reduced size as well as presence of hierarchical structures [7]. The less M S for these two samples compared with that for bulk nickel materials (55 emu/g) is mainly due to the spin disorder on the surface and surface oxidation [2]. The M-H hysteresis loops of two nickel samples are all symmetric in shape with respect to zero magnetic field.…”
Section: (B3) (C2) and (C3))mentioning
confidence: 77%
“…Nanoscale metal materials with different dimensions and shapes have attracted intensive interest due to their excellent electronic, magnetic, catalytic, optical properties and promising applications in many fields such as high-density magnetic recording, catalysis, biological labeling, optoelectronics, surface-enhanced Raman scattering (SERS), and so on [1][2][3][4][5]. During the past several years, various morphologies of nanoscale nickel (Ni) such as nanoparticles, nanoplates, hexagonal nanodisks, nanotubes, nanowires, hollow octahedrons, concave polyhedrons, nanowalls and nanostrips, have indeed been synthesized [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…with an average length of 10 ȝP and a diameter of about 200 nm, using PEG and CTAB surfactant in a sealed autoclave under an external magnetic field, under high temperature and pressure [16]. Although Gong et al synthesized Ni nanowires under normal pressure, ethylene glycol was used as the solvent [17].…”
Section: Recently Niu Et Al Fabricated Acicular Nickel Nanocrystallitesmentioning
confidence: 99%